2018
DOI: 10.1186/s13046-018-0856-6
|View full text |Cite
|
Sign up to set email alerts
|

TSSC3 promotes autophagy via inactivating the Src-mediated PI3K/Akt/mTOR pathway to suppress tumorigenesis and metastasis in osteosarcoma, and predicts a favorable prognosis

Abstract: BackgroundOver the last two or three decades, the pace of development of treatments for osteosarcoma tends has been slow. Novel effective therapies for osteosarcoma are still lacking. Previously, we reported that tumor-suppressing STF cDNA 3 (TSSC3) functions as an imprinted tumor suppressor gene in osteosarcoma; however, the underlying mechanism by which TSSC3 suppresses the tumorigenesis and metastasis remain unclear.MethodsWe investigated the dynamic expression patterns of TSSC3 and autophagy-related protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 49 publications
3
80
0
Order By: Relevance
“…In contrast, Gugnoni et al 30 reported that preventing autophagy could lead to EMT and cancer metastasis. Another study also confirmed that autophagy inhibited EMT and may lead to reversion of the EMT phenotype in cancer cells 63 . In order to examine the underlying relationship between OS cells and EMT, we silenced ATG5, which is recognized to have an essential role in autophagosome formation.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, Gugnoni et al 30 reported that preventing autophagy could lead to EMT and cancer metastasis. Another study also confirmed that autophagy inhibited EMT and may lead to reversion of the EMT phenotype in cancer cells 63 . In order to examine the underlying relationship between OS cells and EMT, we silenced ATG5, which is recognized to have an essential role in autophagosome formation.…”
Section: Discussionmentioning
confidence: 71%
“…Autophagy is known to be involved in tumor progression (26,27). In order to elucidate the effect of Aurora-B inhibition induced autophagy on the metastasis of OS cells, wound healing, transwell migration and invasion assays were performed to detect migration and invasion ability of OS cells.…”
Section: Resultsmentioning
confidence: 99%
“…These ndings indicate that autophagy plays an essential role in the process of Aurora-B affecting the ability of motility and invasive in OS cells. Autophagy is reported to inhibit cell migration by accelerating the degradation of MMP family proteins (26,27), therefore, we sought to determine the MMP2 protein levels in Aurora-Bknockdown OS cells with or without CQ treatment. Results showed that the suppression of MMP2 expression due to Aurora-B knockdown could be restored by CQ treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The non-receptor tyrosine kinase Src has been involved in multiple cancer-related process including proliferation and survival through Src-mediated PI3K/AKT/mTOR, MAPK/ ERK and JAK/STAT3 signaling [27][28][29], therefore it has been recently indicated as a promising therapeutic target in the treatment of solid tumors including ESCC [30]. In addition, it has been reported that Src is not only involved in tumor progression but also associated with the resistance to anticancer drugs in traditional and targeted therapies [31].…”
Section: Discussionmentioning
confidence: 99%